Yield and yield components of Arachis hypogaea L. as influenced by NPK chemical fertilizers, farm yard manure and gypsum (Bangladesh Journal of Scientific and Industrial Research, 2016)
Field trials were conducted to evaluate the effect of chemical fertilizers, farmyard manure (FYM) and gypsum on yield and yield components of groundnut (Arachis hypogea L.). There were nine treatments included unfertilized treatment and full doses of recommended NPK fertilizers (65:100:75 kg/ha) or reduced doses of recommended NPK fertilizers (30:50:37.5 kg/ha) and FYM@10 t/ha in combination with different levels (0, 150, 300 and 450 kg/ha) of gypsum. The results exhibited that full dose of NPK fertilizers with 300 kg/ha gypsum treatment gave significantly (P